(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Homonyms and polysemy are two linguistic concepts that often confuse people. Homonyms are words that are spelled and pronounced the same but have different meanings, while polysemous words have more than one related meaning. words are spoken. This article explores the differences between homonyms and polysemy, gives examples of each, and discusses their importance in language and communication